2014
DOI: 10.1523/jneurosci.0514-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Shifts in the Balance of Excitation and Inhibition Coordinate the Activity of Axial Motor Pools at Different Speeds of Locomotion

Abstract: An emerging consensus from studies of axial and limb networks is that different premotor populations are required for different speeds of locomotion. An important but unresolved issue is why this occurs. Here, we perform voltage-clamp recordings from axial motoneurons in larval zebrafish during "fictive" swimming to test the idea that systematic differences in the biophysical properties of axial motoneurons are associated with differential tuning in the weight and timing of synaptic drive, which would help exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 45 publications
(15 reference statements)
6
60
0
Order By: Relevance
“…2A). A recent study using voltage-clamp recordings in larval zebrafish has begun to elucidate the synaptic basis for synchronizing activity among heterogeneous motor neurons during rhythmic locomotion [19]. In particular, increases in the frequency of fictive swimming are associated with a preferential increase in excitatory drive to less excitable motor neurons (Fig.…”
Section: Speed Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…2A). A recent study using voltage-clamp recordings in larval zebrafish has begun to elucidate the synaptic basis for synchronizing activity among heterogeneous motor neurons during rhythmic locomotion [19]. In particular, increases in the frequency of fictive swimming are associated with a preferential increase in excitatory drive to less excitable motor neurons (Fig.…”
Section: Speed Controlmentioning
confidence: 99%
“…A recent anatomical study in larvae has demonstrated that more dorsal V2a neurons have the potential to make systematically more connections to less-excitable motor neurons by virtue of convergent intersegmental axonal projections [24]. This could provide the observed bias in rhythmic excitation during faster swimming [19]. In juvenile/adult zebrafish young enough to use Chx10 expression to identify V2a neurons [25], the spatial recruitment pattern is obscured by neuronal migration, but there are still differences in V2a activation patterns from low to medium frequencies of swimming evoked by bulk electrical stimulation [26].…”
Section: Speed Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…by blocking inhibition (Dichter and Ayala, 1987; Bazhenov et al, 2008). The concept of balanced excitation (E) and inhibition (I) (balanced networks in short) was introduced two decades ago (Shadlen and Newsome, 1994; van Vreeswijk and Sompolinsky, 1996) and has sparked numerous studies both theoretical (Amit and Brunel, 1997; Ozeki et al, 2009; van Vreeswijk and Sompolinsky, 1998; Kumar et al, 2008) as well as experimental (Berg et al, 2007; Okun and Lampl, 2008; Higley and Contreras, 2006; Wehr and Zador, 2003; Kishore et al, 2014). The primary purpose of theoretical models of balanced networks was initially to understand irregular spiking, which was widely observed in experiments (Bell et al, 1995; Shadlen and Newsome, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Within the axial motoneuron pool in the zebrafish spinal cord, early born, large primary motoneurons (PMns) have lower input resistance (Rin) and require larger currents to be recruited; later born, smaller secondary motoneurons (SMns) have higher Rin and can be activated by smaller input currents [510]. Anatomical studies have shown that PMns and SMns have various axonal projection patterns to skeletal muscles [8, 11].…”
Section: Resultsmentioning
confidence: 99%